Association of DYRK1A polymorphisms with sporadic Parkinson's disease in Chinese Han population. (6th October 2016) - Cen, Luan; Xiao, Yousheng; Wei, Lei; Mo, Mingshu; Chen, Xiang; Li, Shaomin; Yang, Xingling; Huang, Qinghui; Qu, Shaogang; Pei, Zhong; Xu, Pingyi
Highlights: α-Synuclein aggregation in Lewy Bodies is a pathological hallmark of PD. DYRK1A phosphorylates α-synuclein and enhances its neurotoxicity to DA neurons. We investigated the genetic variation of DYRK1A in sporadic Chinese PD patients. TT genotype of rs8126696 is a potential risk factor of PD in Chinese Han population. Abstract: α-Synuclein plays important roles in the development of Parkinson's disease (PD) pathologies. The dual-specificity tyrosine phosphorylation-regulated kinase 1A (DYRK1A) has a wide range of phosphorylation targets including α-synuclein. Posphorylated α-synuclein is more neurotoxic to dopamine (DA) neurons, but little is known about the genetic variation of DYRK1A in patients with PD. The present investigation aimed to explore the possible association of DYRK1A gene with PD in Chinese Han population. A total of 268 PD patients and 268 healthy-matched individuals in Chinese Han population were enrolled. Genotyping of rs8126696, rs2835740, and rs1137600 single nucleotide polymorphisms (SNPs) were performed on the Sequenom MassARRAY platform. Results revealed TT genotype in SNP rs8126696 denoted a significant difference between PD patients and controls (OR = 1.710, 95% CI = 1.116–2.619, P = 0.014), and the frequency of rs8126696 TT genotype was significantly higher in male PD patients than male controls (OR = 2.012, 95%CI: 1.125–3.599, p = 0.018). The genotypes in rs2835740 and rs1137600 showed no significant difference between PD patients and controls. These results suggest that TT genotype derived from SNP rs8126696 of DYRK1A gene is a possible risk factor for sporadic PD, especially for males in this Chinese Han population.